Leadership style preferences in Bangladesh’s SMEs: A study on transformational, transactional, and laissez-faire leadership - Hossin, Manir; Azam, Shah; Hossain, Shamim (Business, Management and Economics Engineering, 2024)
Purpose – over the years, small and medium enterprises (SMEs) have grappled with the challenge of adopting appropriate leadership styles domestically and globally. This study, thus, seeks to identify the prevalent leadership styles in Bangladesh’s SME sector, with a specific emphasis on transformational, transactional, and laissez-faire leadership.Research methodology – a positivist research approach was employed to collect and analyse a dataset of 410 samples collected through a self-administered questionnaire survey to different SME owners and managers in Bangladesh. Descriptive statistics were employed for data analyses. Findings – the results revealed that generally SMEs are not recognised with universally accepted leadership style in practice in Bangladesh. Instead, leaders tend to employ all three styles based on individual preferences. Additionally, transformational leadership emerged as the most commonly practiced style, followed by transactional and laissez-faire leadership.Research limitations – the study’s applicability is limited to SME owners and managers, specifically those in urban SMEs within a specific region. Thus, the generalisability of the results to employees and SMEs in rural contexts in Bangladesh presents a challenge.Practical implications – the research insights may be used as valuable guidelines for SME owners and managers in conceptualising leadership styles and their practices, especially in Bangladesh’s SME sector.Originality/Value – the originality of this research lies in addressing a critical issue where many struggle to apply suitable leadership approaches in varying situations.